Novel Benzothiazole Derivatives: Synthesis, Anticancer Activity, Density Function Theory (DFT) Study, and ADMET Prediction - Abbas, Layla Jasim; Hussein, Kawkab Ali (Universitas Gadjah Mada, 2024)
Benzothiazole is an amazing small molecule involved in many applications in industrial and pharmaceutical industries to prepare many candidate compounds as effective drugs. In this study, we presented some derivatives of this compound that were prepared easily and quickly with the help of microwaves to minimize time, energy, and finances. The compounds’ cytotoxicity against the two cell lines SK-GT-4 and AMGM5 was examined. The cytotoxic effect of each compound at different concentrations was measured using the MTT assay. Compounds exhibited no potent cytotoxic effects toward the SK-GT-4 cell line. Compounds B1 and B2 had a high IC50 value and good growth inhibition activity against the AMGM5 cell line. According to in silico absorption, distribution, metabolism, and excretion analysis (ADME) prediction studies, the compounds B1, B2, and B3 met Lipinski and were drug-like in most physicochemical parameters. Despite some violations, generally favorable pharmacokinetic properties. It is also assumed that it can potentially become a drug candidate in the future. Various electronic parameters were examined using DFT/WB97XD/6-31++G(d,p), and studies were conducted to support the experimental findings. To estimate the binding modes of compounds B1 and B5, we also performed in silico molecular docking studies.